2016
DOI: 10.1038/srep29840
|View full text |Cite
|
Sign up to set email alerts
|

Designation of highly efficient catalysts for one pot conversion of glycerol to lactic acid

Abstract: Production of lactic acid from glycerol is a cascade catalytic procedure using multifunctional catalysts combined with oxidative and acidic catalytic sites. Therefore, a series of silver-exchanged phosphomolybdic acid catalysts (AgxH3−xPMo12O40, x = 1 ~ 3, abbreviated as AgxPMo) was designed and applied in glycerol oxidation with O2 as an oxidant to produce lactic acid (LA) without adding any base. Among all, total silver exchanged phosphomolybdic acid (Ag3PMo) was found to be the most active one with LA selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…The production of LA from GLY generally requires the oxidation followed by dehydration/rehydration steps (Figure 22). Tao et al developed a bifunctional catalyst by introducing silver to polyoxometalates (POMs) [155]. The authors confirmed that Ag could enhance both the redox potentials for H3PMo12O40 to be suitable to oxidize GLY to DHA X-GLY conversion, DHA-dihydroxyacetone, GlyAl-glyceraldehydes, GlyA-glyceric acid, GlycA-glycolic acid, FA-formic acid, LA-lactic acid.…”
Section: Glycerolmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of LA from GLY generally requires the oxidation followed by dehydration/rehydration steps (Figure 22). Tao et al developed a bifunctional catalyst by introducing silver to polyoxometalates (POMs) [155]. The authors confirmed that Ag could enhance both the redox potentials for H3PMo12O40 to be suitable to oxidize GLY to DHA X-GLY conversion, DHA-dihydroxyacetone, GlyAl-glyceraldehydes, GlyA-glyceric acid, GlycA-glycolic acid, FA-formic acid, LA-lactic acid.…”
Section: Glycerolmentioning
confidence: 99%
“…Proposed tandem reaction pathways for the selective oxidation of glycerol to lactic acid over Ag x PMo catalysts. Reprinted with permission from reference[155]. Copyright 2016 Nature Publishing Group.…”
mentioning
confidence: 99%
“…2). [31][32][33][34] Cascade reactions can improve the atom economy or the E-factor (kg waste /kg product ) by limiting the number of energy-intensive steps needed for the isolation and purification of intermediate products as well as for the catalysts recovery. In this context, the versatile application of multifunctional solid catalysts with adequate amounts of acid, base or redox active sites is essential.…”
Section: Bert F Selsmentioning
confidence: 99%
“…As similar as alkalis, Lewis acids are also capable of catalyzing dehydration and isomerization in the biomass conversion. In particular, numerous achievements of Lewis acid-catalyzed transformation of C 6 and C 3 sugars to lactic acid have already been made [111] in recent year. Therefore, Lewis acid can be expected to combine with dehydrogenation catalysts and applied to the transformation of glycerol to lactic acid.…”
Section: Alkali-free Catalytic Systemsmentioning
confidence: 99%
“…Polyoxometalates (e.g., H 3 PMo 12 O 40 ) are well known as Brønsted acids and redox catalysts, which have a variety of applications for oxidation and acid-catalyzed reactions including the oxidative conversion of glycerol [109] . Through exchange of protons by metal ions, different Lewis acidic sites (e.g., Al 3 + , Ag + ) can be incorporated into polyoxometalates [110,111] . Because both redox sites and Lewis acidic sites co-existed, such metal-substituted polyoxometalates are potential candidates for the oxidative conversion of glycerol that involves dehydrogenation and Lewis acidfacilitated dehydration and rearrangement reactions ( Fig.…”
Section: Alkali-free Catalytic Systemsmentioning
confidence: 99%